Perioperative Certified Nurses Celebrate 20 Years of Specialty Certification - Vachon, Lucie (Operating Room Nurses Association of Canada Journal, 2015)
Every year over 300 perioperative RNs across Canada step up to qualify, or maintain, their perioperative national certification designation. These RNs demonstrate to patients, employers and colleagues that they Care to be the Best in their specialty.